(untitled) (KYAMC Journal, 2019)
Background: Coronary artery bypass surgery (CABG) with cardioplegia has been considered the gold standard operation for coronary revascularization. Activation of compliments system after CABG surgery involves C-reactive protein (CRP). Patients with preoperative increased CRP levels have significantly higher CRP levels on postoperative days and are at increased risk of developing postoperative complications. High sensitivity CRP ( hs-CRP ) is lower concentration of CRP measured by the hs-CRP test. It is more sensitive and more useful in predicting the potential risk level for cardiovascular disease, heart attacks and strokes. Objective: To assess the association of preoperative hs-CRP level with the incidence of postoperative arrhythmia, low output syndrome and sternal wound infection following on pump CABG surgery. Materials & Methods: The study was cross sectional analytical study. A total of 70 patients were selected. For the purpose of analysis the study subjects were divided into two group; Group A patients with preoperative hs-CRP level <3mg/l (n=35) and Group B patients with preoperative hs-CRP level >3mg/l (n=35). The incidence of early outcome- arrhythmia, low output syndrome and sternal wound infection were observed within 30 days of surgical procedure. Results: The incidence of arrhythmia, low output syndrome and sternal wound infection were significantly less in group A than those in group B. Logistic regression analysis showing significant correlation of hs-CRP with arrhythmia, p value is 0.005; with low output syndrome, p value is 0.003 and with sternal wound infection, p value is 0.004. Conclusion: Preoperative hs- CRP is an important determinant of post operative outcome after CABG surgery and might be useful as predictive marker in risk stratification for postoperative complications in patients scheduled for on pump CABG surgery. KYAMC Journal Vol. 9, No.-4, January 2019, Page 153-158